Ideal Double-Track System Construction for Narcotics Abusers in Indonesia - Yaris Adhial Fajrin; Dwi Ratna Indri Hapsari; Nu’man Aunuh; Iga Aprilia (Jurnal Cita Hukum, 2022)
Not only providing benefits for humans, but narcotic substances can also be a threat to the life of a nation if the substance is misused. There are various forms of narcotics abuse (which by Indonesia is categorized as a crime according to Law Number 35 Year 2009), one of which is the act of using/consuming narcotics for own self against the law (illegal). The existence of narcotics abusers for themselves opens up opportunities for perpetrators to experience dependence on these substances or commonly referred to as narcotics addicts. The Indonesia Narcotics Law regulates two forms of sanctions for narcotics abusers for themselves, namely criminal sanctions and treatment sanctions in the form of rehabilitation, which are accommodated in the double-track system model. Through normative legal research methods, this paper will provide an ideal description of the double-track system model in efforts to enforce criminal law for narcotics abusers in Indonesia, so that the sentencing model can effectively solve the dependency problem experienced by perpetrators (narcotics addicts) who are in the process of committing crimes. Indonesian criminal justice.